A Computerized Simulation of the Occlusal Surface in Equine Cheek Teeth: A Simplified Model - Sterkenburgh, Tomas; Schulz-Kornas, Ellen; Nowak, Michael; Staszyk, Carsten (Frontiers in Veterinary Science, 2022)
Equine mastication, as well as dental wear patterns, are highly important for the development of treatments in equine dentistry. During the last decades the stress and strain distributions of equine teeth has been successfully simulated using finite element analysis. Yet, to date, there is no simulation available for dental tooth wear in equines. In this study, we developed a simplified two-dimensional computer simulation of dental wear. It provides a first tentative explanation for the development of the marked physiological inclination of the occlusal surface and for pathological conditions such as sharp enamel points in equine cheek teeth. The mechanical properties of the dental structures as well as the movement of the mandible during the equine chewing cycle were simulated according to previously published data. The simulation setup was optimized in preliminary test runs. Further simulations were conducted varying the lateral excursion of the mandible and the presence or absence of incisor contact during the chewing cycle. The results of simulations showed clear analogies to tooth wear patterns in living equids, including the formation of wear abnormalities. Our analysis indicates that small variations in the pattern of movement during the masticatory cycle, as well as incisor contacts, are leading to marked changes in the occlusal tooth wear patterns. This opens new research avenues to better understand the development of dental wear abnormalities in equines and might have serious implications on captive animal health, welfare, and longevity.